If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + x + -5 = 4x + 4 Reorder the terms: -5 + 4x + x = 4x + 4 Combine like terms: 4x + x = 5x -5 + 5x = 4x + 4 Reorder the terms: -5 + 5x = 4 + 4x Solving -5 + 5x = 4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -5 + 5x + -4x = 4 + 4x + -4x Combine like terms: 5x + -4x = 1x -5 + 1x = 4 + 4x + -4x Combine like terms: 4x + -4x = 0 -5 + 1x = 4 + 0 -5 + 1x = 4 Add '5' to each side of the equation. -5 + 5 + 1x = 4 + 5 Combine like terms: -5 + 5 = 0 0 + 1x = 4 + 5 1x = 4 + 5 Combine like terms: 4 + 5 = 9 1x = 9 Divide each side by '1'. x = 9 Simplifying x = 9
| 4(6t+2)=52 | | -2(21y)= | | 4(6t+2)=53 | | 4(6t+2)=60 | | -2x=-2+8 | | 5x-6=-81 | | 4(6t+2)=4 | | 5x+12-9x=19-15x+11x-7 | | 7x-6x+4x-9x= | | 9+8q=11+7q | | 4(6t+2)=50 | | 4(6t+2)=40 | | 4(6t+2)=28 | | -22(a+6)=-22 | | -3x-2=25 | | 5d-32=8 | | 4r-(-11)=87 | | x/3+4=-2 | | x^4-5x^2-36= | | 10+2(2x-3)=17-(3x-8) | | 3y+78= | | (2x+9)(x+8)=0 | | 8d-22=52 | | 2s+4.6=3s-1.2 | | 5x-32=43 | | 3(m+10)= | | 7x^2=73 | | -5600+200x=0 | | -7(z+4)+3z= | | g-0+4g+6=12 | | 2x*1=x+4 | | -x^2+18x-65=0 |